THE EFFECTIVENES OF FISH BOWL OR FISH BOWL TECHNIQUES TO IMPROVE THE LEARNING OUTCOMES OF IPS IN GRADE STUDENTS V A SND 16 CAKRANEGARA ACADEMIC YEAR 2016/2017 - Ni Komang Sri Widari; Nur hasanah; Siti Istiningsih (Yayasan Pendidikan Intan Cendekia, 2018)
Background of this research is the low social learning outcomes on students fifth grade at SDN 16 Cakranegara, it is caused by learning process focus on teaccher (Teacher Centered) and they used monoton method. Teacher usually teach only usuhg speech method and they didn’t support by the appropriate facilities. The problem in this research is how the efectivness of bowl fish teachnique could improve social learning outcomes on fifth grade students at SDN 16 Cakranegara in 2016 to 2017 ? The purpose is to improve social learning outcomes on fifth grade students in 2016 to 2017 by using bowl fish technique or aquarum. This is a base calssrom research in two cydes each cycle consist of planning, implementation, action, observation,and evaluation, reflection as well. The method collecting data are observation, documentation and test. In the frist cycle the result is on average 75,375 with percentage 70,83% and the scores for activities of students are 53 categories active enough. In second cycle the students having an increase on average 82,791 categories active. The conelusion is the efectivness of bowl fish technique could improve social learing outcomes on fifth grade students at SDN 16 Cakranegara in 2016 to 2017.